Infection prevention in sarcoidosis: proposal for vaccination and prophylactic therapy - Syed, Huzaefah; Ascoli, Christian; Linssen, Catharina; Vagts, Christen; Iden, Thomas; Syed, Aamer; Kron, Jordana; Polly, Kelly; Perkins, David; Finn, Patricia; Novak, Richard; Drent, Marjolein; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Sarcoidosis is a systemic inflammatory disease characterized by granuloma formation in affected organs and caused by dysregulated immune response to an unknown antigen. Sarcoidosis patients receiving immunosuppressive medications are at increased risk of infection. Lymphopenia is also commonly seen among patient with sarcoidosis. In this review, risk of infections, including opportunistic infections, will be outlined. Recommendations for vaccinations and prophylactic therapy based on literature review will also be summarized.